Should They Stay or Should They Go? How the 2017 U.S. Travel Ban Affects International Doctoral Students. (September 2020) - Todoran, Corina; Peterson, Claudette
In the wake of the U.S. government's executive orders restricting travel from six Muslim-majority countries (Iran, Libya, Somalia, Sudan, Syria, and Yemen) in January 2017, we collected data from four focus groups consisting of international doctoral students aiming to provide insight on the following research question: How do international doctoral students make sense of the U.S. political climate on their lived experiences? This article contributes to the literature by discussing a timely issue concerning international students in the United States and points out that the 2017 travel ban has affected not only international doctoral students from those banned countries but has also alarmed students from other countries, who described the climate as stressful, confusing, and hostile. Several students changed their travel plans for conferences or family visits being worried that they might not be able to reenter the United States. Other students feared the immigration rules might suddenly change and affect their visa status. Students also expressed their concerns in regard to job prospects after graduation. This article derives from a larger qualitative study exploring the experiences of international doctoral students in the U.S. academic and cultural settings.